Bioethanol production from lettuce leaves waste by using Saccharomyces cerevisiae - Mustafa, Sama A.; Mohammed, Ahmed J. (Iraqi Journal of Science, 2025)
An investigation was conducted to examine the potential for producing bioethanol from lettuce leaves waste through fermentation utilizing Saccharomyces cerevisiae. In this study three different of pre-treatments methods were applied to the raw materials using H2SO4 (2%), HCl (5%) and NaOH (1%), respectively. The goal of these pretreatments was to break down the cellulose, hemicellulose as well as lignin to a mono-sugar that considered a simpler form which can be consumed directly through the fermentation process by S. cerevisiae to produce bioethanol. The results indicate that the NaOH pre-treatment yielded the highest sugar content, followed by the HCL, H2SO4 pre-treatment, while the untreated samples had the lowest sugar content. The concentrations of ethanol were reported every two days through the fermentation period by using ethanol sensor and the highest ethanol was measured for the samples pre-treated with HCL, followed by samples without pre-treatment, samples pre-treated with H2SO4, and finally, the NaOH-pre-treated samples, which had the lowest ethanol concentration, as measured by an ethanol sensor every two days during the fermentation period. The concentrations of ethanol were also measured by using the High-Performance Liquid Chromatography (HPLC) technique after the first and second distillation, the distillation process was carried out in order to enhance the purity of the bioethanol.